Unmeployment in the transition economies - causes and proposals - Mirjana Dragičević; Alka Obadić (European Regional Science Association (ERSA), 2001)
The main purposes of this paper are: -to analyse unemployment problem in the new transition economies focusing on Croatian case; - to recommend some policies in order to reduce unemployment and to enhance Croatian chances to a successful economic development. The unemployment problem in the transition economies differs by its origin, structure and consequences.During the transition to a market economy (in a last ten years), Bulgaria, Romania, Poland, Hungary and Slovak Republic were all experiencing rates of unemployment of 10 to 16%. The situation is even worse in Croatia were in that period inemployment rate increased from 9% to 21%. That is the reason why the solving of the unemployment problem in Croatia is more complex and should be recognized as one of the main macroeconomic priorities.
Keywords: 330